2009
DOI: 10.1021/la9013398
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Rheology of a Confined Adsorbed Polymer Layer

Abstract: The sliding dynamics of a confined adsorbed polymer layer is investigated at the nanoscale. A combined mechanical and physical approach is used to model the rheology and structure of the adsorbed layer. The confinement at short distances governs the nanotribological behavior of the polymer layer formed close to the surface. It appears that the Amontons' proportionality between frictional and normal stresses does not hold here: the higher the contact pressure, the lower the friction. Besides, the sliding stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…On the other hand, since PMA-COOH is a functionalized organic polymer having an average molecular weight of 20,000 and a number of functional groups that act as adsorption sites, the multiple-point adsorption occurring at these functional groups probably promoted the formation of highly-dense, bulky film that was unlikely to desorb. This bulky film was capable of not only enhancing the viscosity of the oil at the contact but also providing a load-bearing performance that was not dependent on the orientation of the adsorbed molecules [8][9][10][11][15][16][17]. The differences in morphology of the adsorbed film were reflected in their friction characteristics, as a result, there were significant differences in the friction characteristics between the additives.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, since PMA-COOH is a functionalized organic polymer having an average molecular weight of 20,000 and a number of functional groups that act as adsorption sites, the multiple-point adsorption occurring at these functional groups probably promoted the formation of highly-dense, bulky film that was unlikely to desorb. This bulky film was capable of not only enhancing the viscosity of the oil at the contact but also providing a load-bearing performance that was not dependent on the orientation of the adsorbed molecules [8][9][10][11][15][16][17]. The differences in morphology of the adsorbed film were reflected in their friction characteristics, as a result, there were significant differences in the friction characteristics between the additives.…”
Section: Resultsmentioning
confidence: 98%
“…11 Various apparatus were developed to measure contact forces under oscillating conditions. Under moderate applied contact pressure (<50 MPa), the friction dynamics of selfassembled monolayers 12 and polymer layers 13 were analysed using the Ecole centrale de Lyon-Surface Force Apparatus (SFA). With this device, simultaneous normal and tangential oscillating displacements at the picometer scale can also be used to get the rheological behavior of confined molecular films.…”
Section: Introductionmentioning
confidence: 99%
“…Microscale and nanoscale-confined liquids play a fundamental role in many fields, including microfluidics, microchips and boundary lubrication [1][2][3][4][5][6]. As the confinement scale decreases to the molecular size of the liquids, the properties of the liquid film may differ significantly from those of the bulk liquid, including a layering structure and oscillation in density [1], solidlike transition [3] or significantly increased effective viscosity [5].…”
Section: Introductionmentioning
confidence: 99%
“…As the confinement scale decreases to the molecular size of the liquids, the properties of the liquid film may differ significantly from those of the bulk liquid, including a layering structure and oscillation in density [1], solidlike transition [3] or significantly increased effective viscosity [5]. In the past few decades, many pioneering experimental and theoretical studies have focused on the unique properties of confined liquids and their mechanisms [1][2][3][4][5][6][7][8][9]. In the field of tribology, numerous studies have demonstrated that the confinementinduced disordering-ordering transition of lubricant improves the lubrication properties of the liquid [1,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation